The Effect of Butterfly Pea Extract on Blood Glucose Levels in White Rats with Metabolic Syndrome Model - Gunawan, Olivia; Andri Putranto, R. Prihandjojo; Subandono, Jarot; Ika Budiastuti, Veronika (Smart Medical Journal, 2023)
Introduction: Metabolic syndrome is an accumulation of several disorders, one of which is hyperglycemia. Clitoria ternatea is a plant that contains lots of flavonoids and is known to reduce blood glucose levels in metabolic syndrome. This study aimed to determine the effect of butterfly pea extract (Clitoria ternatea) on blood glucose levels in white rats with metabolic syndrome models.Methods: This research is an experimental study using animal models with pre and post-test control group design method. The number of samples was 30 male white rats which were divided into 5 groups: group 1–negative control group; group 2–positive control group; group 3, group 4, and group 5 were the metabolic syndrome group which was given Clitoria ternatea extract with doses of 100, 200, and 400 mg/kgBW, respectively for 28 days. Measurement of blood glucose levels for all groups was carried out on the 36th day as the pre-test and the 64th day as the post-test. Blood glucose levels were obtained through retroorbital venous blood which was analyzed with the Easy Touch blood glucose stick meter. One-way ANOVA was used to analyze data, followed by post-hoc LSD test, and paired T-test.Results: The average post-test random blood glucose levels decreased by 135.16 mg/dl, 163.18 mg/dl, and 168.35 mg/dl. There was a significant difference (p<0.05) between the pre-test and post-test blood glucose levels along with the average blood glucose level amongst groups.Conclusion: Butterfly pea (Clitoria ternatea) could decrease blood glucose levels and cause further decrease with higher doses.